Biosorption optimization and mechanism of biochar from exhausted coffee husk on iron in aqueous solution using response surface methodology - Aninda T. Puari; Arti Azora; Rusnam Rusnam; Nika R. Yanti (Case Studies in Chemical and Environmental Engineering)
The primary goal of the current research was predicting the optimum operational parameters for removing of Fe (II) from aqueous solutions by Exhausted Coffee Husk (ECH) biochar, through batch mode experiments using a Box-Behnken Design (BBD) within a Response Surface Methodology (RSM) framework. The effect operational factors for instance, pH, contact time and the dosage of ECH-biochar were investigated in a certain range, prior to conducting the BBD experiments. The pH was in a range of 4–9, while the contact time was in between 30 and 150 minutes and the dosage 0.05–2.5 g. The results showed that the optimum operational parameters for ECH biochar as biosorbent for Fe ions removal were 7, 0.102 g, 54.49 minutes for pH, contact time and dosage, respectively, with the RE and biosorption capacity (qt) were 99.91 % and 73.09 mg/g. The validation test showed the similar results were obtained for RE and qt with %RSD were 0.7 %. The process of Fe biosorption corresponds effectively with a modified Langmuir isotherm model, and the prediction of the rate constant is reliably achieved using the pseudo-second-order kinetic model. Furthermore, analyses of scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) and X-ray diffraction (XRD) showed ion exchange as the Fe removal mechanism by the ECH-BC, while Fourier-transform infrared spectroscopy (FT-IR) also showed the role of structural alterations on the surface of ECH-BC subsequent to the biosorption of Fe.